Global Modern Oasis Design Innovation through Reviving Ancient Egyptian Gardens - Shamsieva Rafoat Aslidinovna (Universitas Muhammadiyah Sidoarjo, 2024)
This study bridges this gap by exploring the origins, composition, and cultural significance of Egyptian gardens. Through a multidisciplinary approach combining historical analysis and botanical research, we uncover the intricate interplay between trees, vegetables, and flowers within these gardens. Our findings reveal a sophisticated horticultural tradition, where lilies, roses, and various herbs held symbolic and practical importance. Furthermore, drawing parallels between ancient practices and modern landscaping, we propose the integration of Egyptian garden motifs into contemporary park designs in Uzbekistan. By blending historical inspiration with innovative techniques, this endeavor not only enriches the aesthetic landscape but also honors the rich heritage of Eastern civilizations, fostering cultural exchange and appreciation. Highlights: Multidisciplinary approach: Integrating historical analysis and botanical research unveils the complex composition and cultural significance of ancient Egyptian gardens. Symbolic flora: Lilies, roses, and herbs not only adorned Egyptian gardens but held profound symbolic and practical importance, reflecting religious and societal values. Contemporary integration: Proposing the incorporation of Egyptian garden motifs into modern park designs in Uzbekistan fosters cultural exchange and enriches the aesthetic landscape, honoring Eastern civilizations' rich heritage. Keywords: Ancient Egyptian, Horticultural Tradition, Cultural Heritage